Turning Classroom Project into Textbook Design in English for Specific Purposes Subject - Munir, Sirajul (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
This article discusses my experience in shaping EFL learners’ project on textbook design in teaching English for Specific Purposes (ESP) subject. This task was challenging since the learners’ project designing textbook was in the sixth semester students. This article first explores the concept of ESP, principles in developing materials and classroom project. Then, it goes to focus on the pedagogical procedure for designing ESP textbook. This procedure includes (1) prior to designing a textbook; (2) designing a draft of the textbook; (3) finalization of designing textbook; and (4) demonstrating peer teaching on one of the units of the textbook. Finally, it elaborates students’ responses to these practices. The findings show that classroom project can enhance learners’ to good cooperation, improve learners’ knowledge and creativity, and promote learners individual and social values to improve their harmony in life. For future researchers, it is suggested exploring the effect of classroom project on students’ achievement, and to examine the correlation between classroom project on ESP subject and learners’ social values.